2012
DOI: 10.5101/nbe.v4i1.p12-16
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles from Sargassum Tenerrimum and Screening Phytochemicals for Its Antibacterial Activity

Abstract: Synthesis of nanomaterials by biological approach is innovative, cheaper and environmental friendly and requires less-labor. In this regard, the present study focused on the synthesis of silver nanoparticles from the extract of Sargassum tenerrimum. Synthesized silver nanoparticles were wellcharacterized by UV-Visible Spectroscopy (UV-Vis), Fourier-Transform Infra-red Spectroscopy (FT-IR), Transmission Electron Microscopy analysis (TEM) and Dynamic Light Scattering (DLS). It was found that spherical shaped nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 22 publications
12
36
0
Order By: Relevance
“…The UVvisible absorption spectrum of the reaction mixture was analyzed at different wavelengths ranging from 400 to 700 nm. The characteristic absorption peak at 450 nm in UV-Visible spectrum confirmed the formation of AgNPs [16,17]. The broad peak indicates the presence of nanoparticles with a large size distribution as well as polydispersity nature of the particle [18].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The UVvisible absorption spectrum of the reaction mixture was analyzed at different wavelengths ranging from 400 to 700 nm. The characteristic absorption peak at 450 nm in UV-Visible spectrum confirmed the formation of AgNPs [16,17]. The broad peak indicates the presence of nanoparticles with a large size distribution as well as polydispersity nature of the particle [18].…”
Section: Discussionmentioning
confidence: 81%
“…A strong absorption peak at 3,430 cm -1 indicates the presence of phenols and alcohols with the free O-H group. The peak at 1,644 cm -1 represents the presence of amide I group and may well arise due to the carbonyl stretch in proteins [17]. Absorbance bands were seen at 3410 cm -1 were assigned to the stretching vibrations of primary and secondary amines, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The observed band in this range has been associated with Ag-NPs confirming the synthesis of spherical Ag-NPs with narrow size distribution (Kumar et al, 2012). The microstructure characterization of Ag-NPs was carried out using SEM showed that the Ag-NPs were in narrow size range, with most of the particles with size of 32 and 43nm.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we have synthesized silver nanoparticles rapidly at 15 minutes using the extract of P. tetrastromatica. Similarly, Kumar et al [12] synthesized silver nanoparticles within 20 minutes by using the extract of Sargassum tenerrimum and Singaravelu et al, [7] synthesized gold nanoparticles after the 24 hrs incubation time using Sargassum wightii.…”
Section: Discussionmentioning
confidence: 99%